Exploring the mechanistic role of alloying elements in copper-based electrocatalysts for the reduction of carbon dioxide to methane - Hao, Mingzhong; Duan, Baorong; Leng, Guorui; Liu, Junjie; Li, Song; Wang, Shanshan; Qu, Jiale (Frontiers in Chemistry, 2023)
The promise of electrochemically reducing excess anthropogenic carbon dioxide into useful chemicals and fuels has gained appreciable interest. Indium-copper (In-Cu) alloys have recently attracted attention as prospective catalysts for the carbon dioxide reduction reaction (CO2RR), though they chiefly yield carbon monoxide. Generating further reduced C1 species such as methane remains elusive due to limited understanding of how In-Cu alloying impacts electrocatalysis. In this work, we employed first-principles simulations to investigate In-Cu alloys for CO2RR to methane.Compared with pure copper, In-Cu alloys suppress the hydrogen evolution reaction while demonstrating superior initial CO2RR selectivity. Among alloys studied, In7Cu10 exhibited the most promising catalytic potential, with a limiting potential of -0.54 V vs.the reversible hydrogen electrode. Analyses of adsorbed geometries and electronic structures suggest this decreased overpotential arises primarily from electronic perturbations around copper and indium ions, and carbon-oxygen bond stability. This study outlines a rational strategy to modulate metal alloy compositions and design synergistic CO2RR catalysts possessing appreciable activity and selectivity.